Intelligent Reflecting Surfaces Adaptive Beamsteering and PSK Direct Modulation - Muhammad Miftahul Amri; Ghafar Ramadhan Faqih (Engineering Science Letter, 2022)
Intelligent Reflecting Surfaces (IRS), a planar array consisting of a large number of low-cost and low-complexity metal patch elements, is predicted to be among the key technologies in future wireless communications. This is mainly due to its capability to improve wireless energy and spectrum efficiency by reconfiguring the wireless environment in a smart and flexible way. IRS is capable of shifting the phase, amplitude, frequency, or even polarity of the impinging electromagnetic (EM) wave. However, only the phase-shift type of IRS is widely adopted in most scenarios. In this paper, we exploit the property of such IRS to directly modulate an incident EM wave with phase shift keying (PSK) modulation. We consider one transmit antenna that transmits a continuous single-tone electromagnetic (EM) wave, which is then modulated by the IRS and reflected toward the receiver. In addition to the theoretical explanation, we present simulation results with different modulation orders. Moreover, we validated the simulation results by experiment. Furthermore, we also proposed a beam scanning method to obtain IRS patterns to steer the beam towards the desired direction in an adaptive manner. One optimal pattern that maximizes the received power is then selected from the beam scanning codebook. By doing so, a wireless path strength can be significantly improved.